Mechanics and Control of Solids and Structures - Polyanskiy, Vladimir A.; K. Belyaev, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a collection of papers prepared by the researches of the Institute for Problems in Mechanical Engineering of the Russian Academy of Sciences (IPME RAS) on the occasion of the 30th anniversary of the establishment of the Institute. The IPME RAS is one of the leading research institutes of the Russian Academy of Sciences and consists of 18 research units (laboratories). The chapters cover the main research directions of the institute, including nano-,micro-, meso- and macro- mechanics and materials, with ,special emphasis on the problems of strength of materials and service life of structures. .
Chapter 1. Solution of dynamic boundary problems for plane deformation in nonlinear model of crystal media with complex lattice -- Chapter 2. Equilibrium structures and flows of polar and nonpolar fluids in nanoscopic channels -- Chapter 3. Boundary-value problems for defects in nanoscale and nanocomposite solids -- Chapter 4. Micromechanics of strength and plasticity in nanostructured materials -- Chapter 5. Nanoscale SiC on silicon - a new platform for growth of wide-bandgap semiconductors.
Keywords: Mechanics, Applied; Engineering Mechanics; Mechanical engineering; Mechanics -- Mathematical models